Kontribusi Ekonomi Syariah dalam Mewujudkan toleransi dan Kerukunan Antar Umat Beragama - Vernon, Annisa Della; Aini, Anisa Nur; Himayah, Uti (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research plays an important role in contributing to Islamic economics in realizing tolerance and harmony between religious communities. The purpose of this study is to explore how Islamic economic principles can facilitate positive interactions between different communities. The method employed is a literature review, analyzing pre-existing written sources to address the research problem. The results indicate that Islamic economics, through the practices of sharing, social justice, and transparency, fosters an environment conducive to harmony among people. The discussion reveals that the implementation of Islamic economics can reduce the potential for conflict and enhance collaboration between religions. The conclusion confirms that Islamic economics is not merely an economic tool, but also a means to strengthen tolerance and harmony in a pluralistic society.